TINDAKAN HUKUM YANG DAPAT DILAKUKAN OLEH PEMEGANG SAHAM MINORITAS DALAM MELINDUNGI HAK SEBAGAI PEMEGANG SAHAM - Yobel, Matthew Aurellio (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2022)
Minority shareholders are part of an important element of a company. The continuity of work practices that occur often do not run according to expectations, the legal certainty received by minority shareholders is not the same as the majority shareholders who have enormous power in the company. Therefore, legal protection is needed to protect the rights of minority shareholders. In this study, the author uses a normative juridical research method with a statutory approach and also a conceptual approach. The author also uses legal materials or data obtained by the Library study method, with primary material in the form of laws and regulations, and also for secondary materials using research results with the same or related themes. The results of the research that the authors get are that legal protection for minority shareholders is still not guaranteed for sure, but there are various ways or actions that can be taken by minority shareholders in earning their rights in the company, one of which is asking for the rights to have their shares purchased at a reasonable price.